THE FUNCTION OF IMAGERY IN CONTEMPORARY POETRY - Yuldasheva Mahinur Baxodir qizi; ABDURAMONOVA DIANA VALERYEVNA (TADQIQOTLAR.UZ, 2024)
Abstract: One of the many strategies used by poets and other authors, whether intentionally or inadvertently, to strengthen their expressions is imagery. Therefore, it is essential that readers understand this literary device, but most readers do not take the use of imagery seriously or explain how it contributes to the successful literary analysis and teaching process. Poetry in particular benefits greatly from the use of "imagery," which stimulates the senses and helps readers understand the message that poets or other authors are trying to convey. Investigating the rationale behind the use of imagery and the degree to which it can further literary analysis and education is the primary concern that motivated this study. Explaining the importance of images in literary analysis and the teaching process is the study’s goal. The article’s references were gathered from a variety of print and internet sources. To support the claim, a qualitative research approach based on secondary sources has been used. According to the study’s findings, any text can become both formally and functionally appealing through the use of imagery.[1] The study also finds that by stimulating readers’ interest and engaging their senses, the employment of imagery in literary texts improves their perceptual capability.